CFD ANALYSIS ON RADIALCOOLING OF GAS TURBINE BLADE - HARSHA D A,; DR.YOGANANDA A, (International Journal of Innovations in Engineering Research and Technology, 2021)
Gas turbines are extensively used for air craft propulsion, land based power generation and industrial applications. Thermal efficiency of gas turbine improved by increasing turbine rotor inlet temperature. The current rotor inlet temperature in advanced gas turbine is for above the melting point of blade material. A sophisticated cooling scheme must be developed for continuous safe operation of gas turbines with high performance. Gas turbines are cooled externally and internally. Several methods have been suggested for the cooling of blades and vanes. The techniques that involve to cool the blades and vanes by using cooling methods is to have radial holes to pass high velocity cooling air along the blade span. In this thesis, a turbine blade is designed and modelled in CATIA v5and ICEM CFDsoftware. The turbine blades are designed using cooling holes. The turbine blade is designed with 12 holes. CFD analysis is done to determine the pressure distribution, velocity, temperature distribution and heat transfer rate by applying the inlet velocities. Thermaland Structural analysis is done to determine the heat transfer rates and strength of the blade. The present used material for blade is chromium steel. In this thesis, itis replaced with Titanium aluminium alloy. The better material for blade is analyzed